Exploring the need of teaching module for enhancing higher-order thinking skills - Mat, Hamidah; Mustakim, Siti Salina; Razali, Fazilah; Ghazali, Norliza; Minghat, Asnul Dahar (Human Resource Management Academic Research Society, 2023)
The purpose of this research is to analyze the necessity for the development of a scientific teaching module based on students' HOTS. Empowerment of HOTS in primary school Science Education is a special requirement to ensure students achieve the 6 student aspirations outlined in the Malaysian Education Development Plan. Specifically, this study explores the problems and needs to develop a teaching module in science subjects that apply Higher Order Thinking Skills (HOTS). The development of this module is based on the ADDIE model which consists of analysis, design, development, evaluation, and implementation phases. This study uses a semi-structured interview method on six Science teachers of the Ministry of Education (MOE) from different schools. The objective of the analysis phase was to identify the need to develop teaching modules for electrical topics under the Science syllabus. To find out the need for the development of the module, an interview was conducted with six science teachers who are experts in the field in the Seremban area. Four themes emerged from the need analysis namely; (1) The importance of learning electrical topics, (2) Problems in the teaching and learning of Science, (3) Teaching strategies, and (4) Desired improvements. The development of this module contributes to teaching and facilitation to improve students' HOTS in primary school science subjects.